Impact of Adjusting Brake Lining Gap and Brake Drum Temperature on Brake Efficiency of Motor Vehicles - Novianto, R. Arief; Achmaditiya, Galuh (RSF Conference Series: Engineering and Technology, 2022)
In motor vehicle systems, brakes are one of the important components that have a major role in reducing the risk of accidents on the highway. In the brake system, especially drum brakes, improper component adjustment can cause the brakes not to work optimally. This research was conducted to determine the impact of large variations in the brake lining gap and brake drum temperature on brake efficiency in motorized vehicles. This study uses an experimental method with variations in the adjustment of the size of the brake lining gap and the temperature of the drum brake. The main brake efficiency was tested using a brake tester from these several variations. The variations of the brake lining gap used are 0.3 mm, 1 mm, and 1.7 mm. Meanwhile, the brake drum temperature is set at 30, 90, and 150 degrees Celsius. The result of this research is that the wider the brake lining gap, the smaller the brake efficiency. The greater the temperature on the drum brake also affects the smaller the efficiency of the brake. Meanwhile, the variable brake lining gap and temperature simultaneously (together) affect the level of brake efficiency. The larger gap between the lining and the temperature of the drum brake, the lower the efficiency of the brake obtained.